Association Between ABO and Both Allergy and Body Mass Index in a Random Sample of High School Students in Al-Bayda City, Libya - Hajir Husayn; Enas Saleh; Nadia Ibrahim (AlQalam Journal of Medical and Applied Sciences, 2025)
The objective of the current study was to investigate blood type distribution and its relationship to body Mass Index (BMI) and allergic diseases. 100 students from Fatat Libya High School in Al-Bayda City, Libya, on 5/2/2025. Weight and height were measured, BMI was calculated, and types of allergies, if any, were recorded for each student individually. The result showed that the individuals with blood group (O+) had the highest number, reaching 35% followed by (A+) 30%, and (B+) group recorded 12%, A- recorded the lowest percentage, 3%, while AB- did not record any percentage. Also, 31 samples had more than one type of allergy, distributed as follows: 19 samples had allergic rhinitis (AR), 7 had chest allergies, 2 had skin allergies (one had a metal allergy(B+) and one had eczema (A+). Also, one case each of nut allergy, eye allergy (O+), and milk allergy (A+) was recorded. Meanwhile, BMI results showed normal body mass, only one sample with a normal BMI of 22.9 was recorded for blood type O+.15 samples were recorded for the first stage of obesity. The number of samples in the second stage of obesity reached 58, representing the largest percentage.26 samples were recorded for the last stage of obesity. Also, there are non-significant differences (p>0.05) in BMI between blood groups recorded in this study. Moreover, there is no significant association between blood type and allergy.